Evaluasi Usability Aplikasi Ibis Paint X Menggunkan Metode System Usability Scale dan User Experience Questionnaire - Asmasudirdja, Amalia Zaini; Mayatopani, Hendra (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Ibis Paint X is a drawing application that is quite in demand, because it has been downloaded by more than 100 million users with around 1.9 million reviews on the Google Play Store. Until now, there has been no research on the usability evaluation of the Ibis Paint X application, so there may be some unknown usability problems. This study aims to evaluate the usability of Ibis Paint X as a digital drawing application that is quite in demand. In evaluating the usability of Ibis Paint X, two usability measurement methods are used, namely the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ). The purpose of using two methods to evaluate the usability of the Ibis Paint X application is to obtain more in-depth evaluation results from two points of view of the usability evaluation method of an application. The evaluation process was assessed by 122 respondents using the Ibis Paint X application. Based on the evaluation results of the SUS method getting a score of 68.69, judging from the interpretation of the SUS score which has 4 categories, it can be concluded that Ibis Paint X gets a